SPECIES DETERMINATION OF GREEN ALGAE ISOLATED FROM JEPARA COASTAL REGION BASED ON MICROBIOLOGICAL, ECOPHYSIOLOGICAL AND MOLECULAR CHARACTERIZATION FOR IMPROVEMENT OF CAROTENOID PRODUCTION - Hermin Pancasakti Kusumaningrum; Endang Kusdiyantini; Triwibowo Yuwono; Joedoro Soedarsono (JOURNAL OF COASTAL DEVELOPMENT, 2006)
A local isolate of green algae called C1 from Jepara waters is usually used as a source for carotenoid supplement for animal fisheries in the local area. This indigenous algae has been successfully purificated.  Although the local isolate was known as eucaryotic green algae Dunaliella, our previous molecular study by 18S rDNA analysis to determine the species of this organisms showed negative result. In order to improve carotenoid production especially detection of biosynthetic pathway from the organisms investigated in this study, the main purpose of this study was species determination of local isolate of green algae based on microbiologycal, ecophysiologycal and molecular characterization. The results of this research  indicated that local isolate of green algae posseses Cyanobacteria characteristic, especially Synechocystis. Analyses with 16S rDNA sequence from genome of green algae isolates were also in accordance with these results, showing close similarities with Synechocystis 16S rDNA sequence.  However, it should be noted that, instead of having Synechocystis dominant feature, it was also found that local isolate of green algae exhibit different characteristic in having chlorophyll a, chlorophyll b and lack of phycobillins. This character was typical for abberant Cyanophyta, Prochlorophyta.